Analysis on the Influence of Assembly Gap on CFRP Assembly Stress Based on Finite Element Method. Issue 1 (March 2020) - Jiang, Qilin; Hou, Junming; Fang, Xiwu; Wang, Hongrui
Abstract: Due to the material properties and forming process of composite laminates, it is difficult to avoid smaller assembly gaps in the assembly process of laminates. In assembly process, liquid gaskets are generally used to compensate the smaller assembly gaps between laminates. Therefore, this paper established the equivalent assembly model of the laminated plate, and used the finite element analysis method to conduct numerical analysis and quantitative research on the mechanical influence of the assembly gap on the laminated plate assembly on the basis of analyzing the typical structure of the wing box. And the results of finite element method are compared with the experiment. This work provides a theoretical support to ensure the assembly quality of composite laminates.